Speciation and mobility of lead in shooting range soils - Kelebemang, R.; Dinake, P.; Sehube, N.; Daniel, B.; Totolo, O.; Laetsang, M. (Chemical speciation and bioavailability, 2017)
The mobility and bioavailability of lead (Pb) in seven military shooting range soils found in eastern and north eastern Botswana were studied using sequential extraction procedure. The different forms of Pb and their reactivity in the soil help explain their speciation, mobility and bioavailability in the environment. Mobility of Pb in the berm soils in all the seven shooting ranges was found to be over 90% implying high Pb lability. The bioavailability index of Pb was in the range 60-90%, an indication that most of the Pb can be available for plant uptake. Sequential extraction studies indicate that the partitioning of Pb was mostly confined to the carbonate compartment in all the shooting ranges. All the seven shooting ranges failed the Synthetic Precipitation Leaching Procedure (SPLP) with SPLP Pb concentrations exceeding United States Environmental Protection Agency (USEPA) 0.015 mg/kg critical level of hazardous waste, posing a pollution threat to surface and groundwater.